The Unique Nature of the Responsibilities of the International Monetary Fund - Guitian, Manuel (Pamphlet Series; Pamphlet Series, ;, 1992)
Bretton Woods constituted the first formal international agreement on a code of conduct applicable for economic transactions among countries that had subscribed to it. This pamphlet focuses on only one aspect of that code of conduct: the norms that have guided the conduct of financial and exchange transactions among countries, as they have been presented in the original Articles of Agreement of the IMF and their subsequent amendments. The paper outlines the fundamental characteristics of the IMF, examines the direct link between surveillance and conditionalilty, explores potential risks and dangers that might compromise certain fundamental features of the institution, and presents a set of ideas and proposals to ensure the activities of the IMF maintain continuity of its institutional uniqueness.